Novel Genetic Locus Influencing Retinal Venular Tortuosity Is Also Associated With Risk of Coronary Artery Disease. Issue 12 (December 2019) - Veluchamy, Abirami; Ballerini, Lucia; Vitart, Veronique; Schraut, Katharina E.; Kirin, Mirna; Campbell, Harry; Joshi, Peter K.; Relan, Devanjali; Harris, Sarah; Brown, Ellie; Vaidya, Suraj S.; Dhillon, Baljean; et al.
Abstract : Objective: The retina may provide readily accessible imaging biomarkers of global cardiovascular health. Increasing evidence suggests variation in retinal vascular traits is highly heritable. This study aimed to identify the genetic determinants of retinal vascular traits. Approach and Results: We conducted a meta-analysis of genome-wide association studies for quantitative retinal vascular traits derived using semi-automatic image analysis of digital retinal photographs from the GoDARTS (Genetics of Diabetes Audit and Research in Tayside; N=1736) and ORCADES (Orkney Complex Disease Study; N=1358) cohorts. We identified a novel genome-wide significant locus at 19q13 ( ACTN4/CAPN12 ) for retinal venular tortuosity ( TortV ), and one at 13q34 ( COL4A2 ) for retinal arteriolar tortuosity ( TortA ); these 2 loci were subsequently confirmed in 3 independent cohorts (Ntotal =1413). In the combined analysis of discovery and replication cohorts, the lead single-nucleotide polymorphism in ACTN4 / CAPN12 was rs1808382 (βs.d. =-0.109; SE=0.015; P =2.39×10- 13 ) and in COL4A2 was rs7991229 (βs.d. =0.103; SE=0.015; P =4.66×10- 12 ). Notably, the ACTN4 / CAPN12 locus associated with TortV is also associated with coronary artery disease, heart rate, and atrial fibrillation. Conclusions: Genetic determinants of retinal vascular tortuosity are also linked to cardiovascular health. These findings provide a molecular pathophysiological foundation for the use of retinal vascular traits as biomarkers for cardiovascular diseases. Abstract : Supplemental Digital Content is available in the text.